Patient Initiated Follow Up for Intellectual Disability Psychiatry Services (Cardiff West): Development of a Quality Improvement Study with Consideration of Patient Reported Experience Measures (PREMs) - Lara Wiggins; Catherine Walton (BJPsych Open)
Aims: The rising caseloads in Swansea Bay University Health Board (SBUHB), with some sector consultants managing over 200 patients, exceed the Royal College of Psychiatrists’ recommended caseload of 100. Patients transitioning into Intellectual Disability Services are increasingly complex and therefore need more intensive support which has compounded the issue. This Quality Improvement (QI) project aimed to: